2018
DOI: 10.5194/bg-15-1293-2018
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of droughts and extreme-temperature events on gross primary production and ecosystem respiration: a systematic assessment across ecosystems and climate zones

Abstract: Abstract. Extreme climatic events, such as droughts and heat stress, induce anomalies in ecosystem–atmosphere CO2 fluxes, such as gross primary production (GPP) and ecosystem respiration (Reco), and, hence, can change the net ecosystem carbon balance. However, despite our increasing understanding of the underlying mechanisms, the magnitudes of the impacts of different types of extremes on GPP and Reco within and between ecosystems remain poorly predicted. Here we aim to identify the major factors controlling t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
127
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 183 publications
(132 citation statements)
references
References 164 publications
5
127
0
Order By: Relevance
“…In our study, 14 (out of 21) ENF sites experienced significant GEP decline with increasing temperature for more than 10 days during summer. Since the study conducted by von Buttlar et al () did not consider the timing of the heat waves, it is very likely that the negative heat impact in summer was offset by the positive impact in spring, resulting in a neutral response of GEP to heat stress in ENF over the yearly basis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 14 (out of 21) ENF sites experienced significant GEP decline with increasing temperature for more than 10 days during summer. Since the study conducted by von Buttlar et al () did not consider the timing of the heat waves, it is very likely that the negative heat impact in summer was offset by the positive impact in spring, resulting in a neutral response of GEP to heat stress in ENF over the yearly basis.…”
Section: Discussionmentioning
confidence: 99%
“…, Buttlar et al. ). Since GEP exhibited weaker correlations with the changes of environmental variables compared with ER (Magnus et al.…”
Section: Discussionmentioning
confidence: 99%
“…Richardson et al (2009) reported that there was no significant relationship between the changes of S/S (date of ecosystem transition from CO 2 source to sink) and the dynamics of spring or annual ER in forests. At the ecosystem level, although GEP has been shown to be positively correlated with ER (Ma et al 2016), GEP and ER responded differently to the changes of temperature and soil moisture (Anderson-Teixeira et al 2015, Buttlar et al 2018. Since GEP exhibited weaker correlations with the changes of environmental variables compared with ER (Magnus et al 2010), the dynamics of ER may be mainly influenced by the environmental variables, and hence, the influences of the changes in spring phenology on ER may be concealed.…”
Section: Differences Among Gep Nep and Er In These Relationshipsmentioning
confidence: 99%
“…Extreme climate events, such as drought and hot extremes, have been occurring on a wide range of time scales and in many parts of the world in relation to climate change (Bates et al, ; Mishra & Singh, ; von Buttlar et al, ). Heat waves cause water loss, lower the yield of agricultural products, increase energy consumption, and adversely affect human health in a variety of direct, indirect, immediate, and delayed ways (Mazdiyasni & Aghakouchak, ; U.S. Department of Energy, ; Zaitchik et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Heat waves cause water loss, lower the yield of agricultural products, increase energy consumption, and adversely affect human health in a variety of direct, indirect, immediate, and delayed ways (Mazdiyasni & Aghakouchak, ; U.S. Department of Energy, ; Zaitchik et al, ). Drought, characterized by less than normal precipitation over a period of months to years (Zhang & Zhou, ), has devastating impacts on the ecological environment and social‐economic sectors, including the urban water supply, modern industries, and also the agricultural production (Food and Agricultural Organisation of United nations (FAO), ; Heim, ; von Buttlar et al, ; World Bank, ). Drought is one of the most expensive natural disasters and causes annual losses estimated at $6–8 billion in the United States (Keyantash & Dracup, ).…”
Section: Introductionmentioning
confidence: 99%